2017
DOI: 10.5937/jrb1707013t
|View full text |Cite
|
Sign up to set email alerts
|

EuReCa 2017: Follow up in Republic of Serbia: Six months report

Abstract: Analiza prikupljenih podataka u 2017. godini i njihovo poređe-nje sa ranijim rezultatima programa EuReCa. Metodologija: Podaci o srčanom zastoju prikupljeni su putem jedinstvenog upitnika EuReCa programa tokom realizacije prospektivne, opservacione studije EuReCa One koja je pod brojem NCT02236819 registrovana u bazi trijala i odobrena od zdravstvenih autoriteta u SAD. Analizirani su podaci iz registra srčanog zastoja Srbija u periodu od 1. januara 2017. godine do 01. jula 2017. Glavni istraživači svake ustano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 3 publications
(3 reference statements)
1
6
3
3
Order By: Relevance
“…4,8 This study reports the comparable annual incidence rate of 83.6/100,000, and previous reports of OHCA incidence in individual years imply that there is significant variability not only in time, but also in geographical distribution as well. [9][10][11] The results of this study are, however, lower than the incidence shown in the 2015 and 2016 reports from Serbia (160/100,000 and 122/100,000, respectively), 9,10 but are higher than the incidence reported from the first-half of 2017 (49.5/100,000). 11 All these reports analyzed data on all-aged patients, just like is the case in this report.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…4,8 This study reports the comparable annual incidence rate of 83.6/100,000, and previous reports of OHCA incidence in individual years imply that there is significant variability not only in time, but also in geographical distribution as well. [9][10][11] The results of this study are, however, lower than the incidence shown in the 2015 and 2016 reports from Serbia (160/100,000 and 122/100,000, respectively), 9,10 but are higher than the incidence reported from the first-half of 2017 (49.5/100,000). 11 All these reports analyzed data on all-aged patients, just like is the case in this report.…”
Section: Discussioncontrasting
confidence: 73%
“…[9][10][11] The results of this study are, however, lower than the incidence shown in the 2015 and 2016 reports from Serbia (160/100,000 and 122/100,000, respectively), 9,10 but are higher than the incidence reported from the first-half of 2017 (49.5/100,000). 11 All these reports analyzed data on all-aged patients, just like is the case in this report.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…U našoj zemlji incidenca vanbolničkog srčanog zastoja, prema podacima programa EuReCa_Srbija, iznosi 99/100.000 stanovnika na godišnjem nivou. 3 Prisustvo očevica kod osoba sa EuReCa događajem, uvećava šansu za započinjanje kardiopulmonalne resuscitacije 2,8 puta. Ne postoji signifikantna razlika između pružanja mera kardiopulmonalne resuscitacije samo kompresijama ili ukoliko se primenjuje potpuna resuscitacija, ventilacija i srčana masaža.…”
Section: Discussionunclassified
“…Praćenjem vanbolničkog srčanog zastoja ustanovljeno je da je traumatski srčani zastoj vodeći uzrok smrti kod populacije mlađe od 40 godina u Republici Srbiji i u svetu . 6,7,8,9,10 Prema našem istraživanju, postoje značajne razlike prema polu u odnosu na broj osoba sa povredama zbrinutih na terenu, te podatak o dominaciji osoba muškog pola sa traumom korelira sa podacima iz referentnih svetskih studija. 11,12,13,14 Naša analiza ukazuje da su traumatizovane žene značajno starije dok je prosečna starost pacijenata sa traumom 53 godine.…”
Section: Diskusijaunclassified